(untitled) (diségno, 2023)
Every image created by Massimo Scolari, be it the representation of a volume, a space, an idea or a feeling, or even just the outcome of a state of mind produced by his imagination, is like a door thrown wide open on his mind. A door always bringing forth fascinating descriptions, generated by engaging adventures of thought. [read more]